Comparative Case Report: Divergent Outcomes in Two Pregnant Women with Intracerebral Hemorrhage Associated with Preeclampsia - Yaleswari Hayu Pertiwi; I Gede Sutaniyasa (SUAN PUBLISHER, 2025)
Preeclampsia is a pregnancy complication that can lead to various serious cerebrovascular complications, including intracerebral hemorrhage (ICH). Although the incidence of ICH in pregnancy is relatively low, this complication can cause high mortality and morbidity. Early diagnosis and rapid intervention are crucial for improving patient prognosis. This report aims to compare two cases of pregnant women with preeclampsia who experienced ICH, to highlight significant differences in clinical outcomes based on the timing of diagnosis and medical intervention. Two cases of ICH in pregnant women with preeclampsia are reported. The first case was diagnosed quickly, and surgical intervention, such as a craniectomy, was performed immediately after diagnosis. In the second case, the diagnosis was delayed, and a more conservative management approach was applied. The clinical outcomes of these two cases are compared, focusing on the time of diagnosis, therapy, and patient outcome. The first case showed a better outcome, with almost complete recovery and minimal disability, after prompt and aggressive medical intervention. Conversely, the second case experienced delays in diagnosis and intervention, which led to the patient's death after undergoing intensive care. Significant differences in the time from symptom onset to diagnosis were found in both cases, contributing to the differing clinical outcomes. Early detection and rapid medical intervention are crucial in managing ICH in pregnant women with preeclampsia. Delays in diagnosis and management can increase the risk of long-term disability or death. Therefore, vigilance for neurological signs in preeclampsia patients and immediate management in a well-equipped facility are highly necessary to improve clinical prognosis.